Body Image Concern for Social Media Users - Ibrahim, Zina Ismail; Jassim, Ahmed L. (Al-Adab Journal, 2022)
body image concern can be defined as: “the negative perceptions and feelings that a person feels towards his body and is affected by factors such as body shape and appearance, attitudes towards weight gain, and cultural norms regarding the ideal body.” The study aimed to identify the extent of concern in the body image among university students, and the statistically significant differences in the interest in their body image according to the gender variable (male - female) and specialization (scientific - human). The researcher adopted the scale (2017). He et al, consisting of (24) paragraphs distributed into six domains, and the researcher undertook a set of measures to prepare the scale for measuring this phenomenon in the Iraqi environment. Truthfulness and consistency were extracted, and discriminatory power was extracted by two methods of the two end groups’ method, and the relationship of the paragraph to the total degree, and to verify the objectives of the research, (200 students from Baghdad University) were selected, and after applying the data and processing it, the results showed the following: The research sample described having an concern in body image. There is no statistically significant difference in the concern in the image of the body according to the gender variable, and there is a statistically significant difference in the concern in the image of the body according to the variable of specialization and in the concern of the scientific. In light of the research results, the researcher puts forth a set of recommendations and proposals, including: Conduct programs that highlight the ideal nature of images and content uploaded to social media and educate young people about the impact that comparisons with this content can have on their excessive concern in their bodies and appearance.